SAT0055 Baricitinib showed rapid and greater reduction in pain compared to adalimumab or placebo in patients with rheumatoid arthritis. (15th June 2017) - Taylor, P; Zhu, B; Gaich, C; Zhang, X; DeLozier, AM; Schlichting, D; Patel, H; Durand, F; Fautrel, B
Abstract : Background: A rapid and meaningful reduction in pain is important to quality of life in patients (pts) with rheumatoid arthritis (RA). Baricitinib (bari) is a selective inhibitor of Janus kinase (JAK)1/JAK 2 in development for pts with active RA. 1 Objectives: To evaluate the effect of bari treatment on pain reduction compared to adalimumab (ADA) or placebo (PBO) in pts with inadequate response to methotrexate (MTX) or biologic disease-modifying antirheumatic drugs (bDMARDs). Methods: In RA-BEAM (NCT01710358 ), 1305 patients with inadequate response to MTX were randomised 3:3:2 to PBO QD, bari 4 mg once daily (QD), or ADA 40 mg biweekly. 2 In RA-BEACON (NCT01721044 ), 527 pts with inadequate response or intolerance to bDMARDs were randomised 1:1:1 to PBO or bari (2 or 4 mg) QD. 3 This post-hoc analysis reports the pts' assessment of pain using a visual analogue scale (VAS, range: 0 to 100 mm). The proportion of pts who achieved pain improvement of ≥30%, ≥50%, and ≥70% of their baseline pain at 1, 2, 4, 8, 12, 16, 20, and 24 weeks of treatment were compared between treatment groups using logistic models adjusted for geographic region, baseline pain score, baseline joint erosion status (RA-BEAM only), and history of bDMARD at screening (RA-BEACON only). Missing data were imputed using modified last observation carried forward. Results: Mean baseline pain scores were 60, 62, and 61 for PBO, bari 4 mg, and ADA, respectively, in RA-BEAM and 65, 62, and 66 for PBO, bari 2 mg, and bari 4 mg, respectively, in RA-BEACON. A significantly greater proportion of pts treated with bari 4 mg achieved ≥30% and ≥50% pain improvement as early as week 1 compared to PBO (both studies) and as early as week 4 compared to ADA (RA-BEAM) (Table). A significant pain improvement of ≥70% was achieved at week 12 for pts treated with bari 4 mg compared to PBO (both studies) and ADA (RA-BEAM). Pain improvement of ≥30%, ≥50%, and ≥70% with bari 2 mg was significant compared to PBO by week 12 (RA-BEACON). Significant improvements in pain for bari vs PBO and bari vs ADA were sustained through week 24. Conclusions: Bari-treated pts reported significantly greater and more rapid reductions in pain severity as measured by the pain VAS compared to PBO or ADA; improvements were sustained through 24 weeks. The results were similar regardless of the pt population. References: Fridman JS, et al. J Immunol 2010;184:5298–307. Taylor PC, et al. Arthritis Rheumatol 2015;67 (suppl 10):abstr 2L. Genovese MC, et al. N Engl J Med 2016;374:1243–52. Disclosure of Interest: P. Taylor Grant/research support from: AbbVie, Bristol Myers Squibb, Celgene, Eli Lilly and Company, Galapagos, GlaxoSmithKline, Merck, Pfizer, UCB, Biogen, Sandoz and Janssen., Consultant for: AbbVie, Bristol Myers Squibb, Celgene, Eli Lilly and Company, Galapagos, GlaxoSmithKline, Merck, Pfizer, UCB, Biogen, Sandoz and Janssen., B. Zhu Employee of: Eli Lilly and Company, C. Gaich Employee of: Eli Lilly and Company, X. Zhang Employee of: Eli Lilly and Company, A. DeLozier Employee of: Eli Lilly and Company, D. Schlichting Employee of: Eli Lilly and Company, H. Patel: None declared, F. Durand: None declared, B. Fautrel Consultant for: AbbVIe, Biogen, BMS, Celgene, Hospira, Janssen, Lilly, Novartis, Pfizer, Roche, SOBI pharma, UCB